PENGARUH KEPERCAYAAN MEREK, KEMUDAHAN PEMBELIAN DAN RISIKO TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Egi Radiansyah; Berlina Anisya Putri (UNIVERSITAS PGRI MADIUN, 2024)
This study aims to analyze the influence of brand trust, convenience, and risk on purchasing decisions. It is a quantitative researchs conducted in Kalianda, Lampung Province, with the entire population of Mamypoko Diapers consumers as the target population. The research sample was selected using a simple random sampling method. Data were collected through the use of a validated and reliability-tested questionnaire. The results of the study indicate that all independent variables, namely brand trust, convenience, and risk, have a positive and significant impact on the dependent variable, which is purchasing decisions.